Comparison of The Learning Culture of Students of SD Muhammadiyah 10 Palembang and SD 02 Lubuk Keliat, Comparative Qualitative Analysis of Learning Culture - Zuhriah, Ifa Datu; Fadhilah Izzah; Putri, Umi Amelia; Fiqriani, Maula; Fauzi, Muhamad; Sukardi, Ismail (Journal of Educational Sciences, 2025)
This research is motivated by the importance of elementary education in shaping students' character and academic abilities. Comparing elementary schools is crucial because choosing a school is a long-term investment for a child's future. This study aims to identify and analyze the factors that contribute to the lack of curriculum adjustment to students' needs, limited teacher time and attention, and low student motivation at SD Muhammadiyah 10 Palembang and SDN 02 Lubuk Keliat. The research method uses a comparative qualitative approach with case studies. The research findings indicate that SD Muhammadiyah 10 excels in the integration of religious values and interactive learning methods, while SDN 02 Lubuk Keliat is more effective in the use of technology. Both schools face challenges such as reading difficulties and classroom management. Improving the quality of education requires a deeper integration of religious values, creative learning methods, effective use of technology, special attention to students with reading difficulties, and structured extracurricular programs. This research is important because it compares two different educational models in the context of elementary schools, which can provide valuable insights for improving the quality of education, addressing specific challenges, and maximizing the unique potential of each school. Collaboration and innovation are needed to create a learning environment that supports students' holistic development.